Effects of Virtual Reality on Static and Dynamic Balance Among Individuals with Down Syndrome - Ghouri, Ebad-ur-Rehman Khan; Memon, Aamir Gul; Ali, Saima; Quratulain Adnan; Saira Tahir (Journal of Liaquat University of Medical & Health Sciences, 2024)
Objective: To determine the effects of virtual reality on static and dynamic balance among individuals with Down syndrome. Methodology: A quasi-experimental study was conducted at Imran Rehabilitation Center, Karachi, Pakistan, from Nov 2020 to April 2021 through a randomized sampling technique. Twenty-four Down syndrome individuals between 6 and 9 years of Age were included. Children who could stand and walk independently, comprehend the instructions and were diagnosed with 50% to 70% IQ level (assessed using the Stanford Binet Intelligence Scale) were included. In contrast, DS children with autism, impaired vision or hearing loss and any associated neurological disorders, i.e. Epilepsy, muscular dystrophies and traumatic brain injury (TBI), were excluded. Data was analyzed using the SPSS version 23. Results: Group A (n=12) participants had a mean age of 8.08±0.79 years, and Group B (n=12) participants had a mean age of 7.61±0.94 years. Both groups had similar gestational Age and IQ levels. The Pediatric Balance Scale (PBS) and Rhomberg test assessed balance and motor control. Within-group analysis revealed significant improvements in both groups for PBS scores. Group analysis did not demonstrate significant differences in the PBS scores or Rhomberg test outcomes. The mean PBS scores for Group A and Group B were 50.33±2.22 and 49.41±3.20, respectively. In the Rhomberg test, no significant differences were found between the two groups with eyes open or closed. Conclusion: The study concluded that static and dynamic balance was significantly improved in both groups; however, virtual reality group intervention showed a more significant improvement in static balance.